Social context may affect urinary excretion of 11-ketotestosterone in African cichlids - Hirschenhauser, K. (2014)
We previously investigated the androgen responsiveness of males to simulated partner and territory intrusions in five African cichlid species (Neolamprologus pulcher, Lamprologus callipterus, Tropheus moorii, Pseudosimochromis curvifrons, Oreochromis mossambicus; Hirschenhauser et al., 2004). Here we re-analysed data on 11 ketotestosterone (11-KT) levels in holding water to compare the free (presumably from the gills) and conjugated (presumably from urine and faeces) 11-KT fractions. We sampled (i) pre-test baseline control levels from individual males in social isolation and (ii) response levels released after social interactions, either with an ovulating female or a male territory intruder. In four out of five species, conjugated metabolites contributed to the observed total 11-KT responses in water during social context, which was particularly apparent in peak responsive individuals exposed to male intruders. Thus, in water from males sampled in isolation immunoreactive 11-KT seemed to derive both from gills and urine, whereas the urinary 11-KT component apparently increased in the social context, particularly when a male was challenged by a same-sex intruder. These results suggest that (i) the social context may affect urine release patterns of males and (ii) 11-KT data acquired by using fish-holding water may not simply reflect the passive transmission of steroid hormones via the gills.